Labuanium vitatum (Crustacea: Decapoda: Brachyura: Sesarmidae), a new Indo-West Pacific species of arboreal crab - Ng, Peter K. L.; Davie, Peter J. F. (Zootaxa, 2011)
A new species of Labuanium Serène & Soh, 1970, L. vitatum is described from northeastern Indian Ocean. It belongs to the L. rotundatum species-group, but is most closely related to L. scandens Ng & Liu, 2003, and L. papuomalesiacum (Nobili, 1899), the latter being here formally removed from synonymy with L. rotundatum (Hess, 1865) and raised to full species status. The new species differs from congeners by numerous characters including the structure of the male first pleopod, carapace and third maxillipeds, and by differences in proportions of the male abdominal somites.